Fusobacterium nucleatum adheres to Clostridioides difficile via the RadD adhesin to enhance biofilm formation in intestinal mucus - Engevik, Melinda A. (Gastroenterology, 2020)
BACKGROUND: Although Clostridioides difficile infection (CDI) is known to involve the disruption of the gut microbiota, little is understood regarding how mucus-associated microbes interact with C. difficile. We hypothesized that select mucus-associated bacteria would promote C. difficile colonization and biofilm formation. METHODS/RESULTS: To create a model of the human intestinal mucus layer and gut microbiota, we used bioreactors inoculated with healthy human feces, treated with clindamycin and infected with C. difficile with the addition of human MUC2-coated coverslips. C. difficile was found to colonize and form biofilms on MUC2-coated coverslips and 16S rRNA sequencing revealed a unique biofilm profile with substantial co-colonization with Fusobacterium. Consistent with our bioreactor data, publicly available datasets and patient stool samples revealed that a subset of patients with C. difficile infection harbored high levels of Fusobacterium. We observed co-localization of C. difficile and F. nucleatum in an aggregation assay using adult patients and pediatric IBD patient stool and in CDI patient tissue sections. C. difficile strains were found to co-aggregate with F. nucleatum subspecies in vitro; an effect that was inhibited by blocking or mutating the adhesin RadD on Fusobacterium and removal of flagella on C. difficile. Aggregation was shown to be unique between F. nucleatum and C. difficile, as other gut commensals did not aggregate with C. difficile. Addition of F. nucleatum also enhanced C. difficile biofilm formation and extracellular polysaccharide production. CONCLUSIONS: Collectively, these data demonstrate a unique interaction of between pathogenic C. difficile and F. nucleatum in the intestinal mucus layer.